Type I J-domain NbMIP1 proteins are required for both Tobacco mosaic virus infection and plant innate immunity. - Yumei Du (Public Library of Science (PLoS), 2013)
Tm-2² is a coiled coil-nucleotide binding-leucine rich repeat resistance protein that confers durable extreme resistance against Tomato mosaic virus (ToMV) and Tobacco mosaic virus (TMV) by recognizing the viral movement protein (MP). Here we report that the Nicotiana benthamiana J-domain MIP1 proteins (NbMIP1s) associate with tobamovirus MP, Tm-2² and SGT1. Silencing of NbMIP1s reduced TMV movement and compromised Tm-2²-mediated resistance against TMV and ToMV. Furthermore, silencing of NbMIP1s reduced the steady-state protein levels of ToMV MP and Tm-2². Moreover, NbMIP1s are required for plant resistance induced by other R genes and the nonhost pathogen Pseudomonas syringae pv. tomato (Pst) DC3000. In addition, we found that SGT1 associates with Tm-2² and is required for Tm-2²-mediated resistance against TMV. These results suggest that NbMIP1s function as co-chaperones during virus infection and plant immunity.